Employee Empowerment Strategy and Strengthening Competence in Improving Employee Performance - Kanya, Nita; Handrian, Feby Ariel; Johan, Ahmad (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Kuningan, 2025)
The purpose of this study was to examine the effect of Employee Empowerment and Competence on Employee Performance. This study uses a census of 44 employees who work at PT Ricky Ptra Globalindo Tbk using descriptive and verification methods. The data collection technique used by researchers is to use primary and secondary data sources in the form of questionnaires given to employees at PT Ricky Putra Globalindo Tbk. The analysis used is path analysis with the help of the SPSS program and hypothesis testing the results of this study indicate that the Employee Empowerment variable is rated fairly well, Competence is rated fairly well and Employee Performance is rated fairly well. The verification results obtained the results that Employee Empowerment affects Employee Performance, Competence affects Employee Performance and there is an influence of Employee Empowerment and Competence on Employee Performance at PT Ricky Putra Globalindo Tbk.